Paese che vai usanza che trovi, tra cosmo e campanile - Pietro Clemente (Archivio Antropologico Mediterraneo)
In the last decades, two big processes have been coexisting in Italy, alongside with the spread of modernization and globalization. The first is the depopulation of many little villages, above all in the inner zone of the country, due to the massive migration of young people to bigger urban centers. The second one is a general rediscovery of the originality and richness of local cultures inherited from the past, that even today mark not only the sense of places and of belonging to them, but constitute a key resource for the younger generations’ imagination of the future and of their dwelling in it. In the lecture, first of all ideally addressed to younger generations, the author retrospectively reflects on his contribution, along the work of many years, to these issues, particularly focusing on his attempt to interweave the Italian school of studies of folklore and anthropology with the attention, in the works of sociologist Giacomo Becattini and the urbanist Alberto Magnaghi, for the new forms of “consciousness of places”, and above all, with James Clifford’s work on the processes of “becoming indigenous in the XXIth Century” in Oceania and the Americas.